Mihály Károlyi and István Bethlen Hungary - Cartledge, Bryan Sir (Haus histories, 2009)
White aster flowers, on sale on the streets of Budapest on the eve of All Souls' Day, are made the symbol of a revolution which brings Mihaly Karolyi (1875-1955) to power at the head of a National Council. Karoly concludes an armistice which leaves large areas of Hungarian territory under occupation by French, Romanian and Serbian forces. Following the King-Emperor's abdication in November 1918, Hungary is declared an independent republic with Karolyi as its President. He sets about meeting Hungary's most pressing social need, for land reform. But Karolyi's liberal regime is soon beset by strong opposition from the right and from the left. The Allies seal Karolyi's fate by refusing to end the economic blockade of Hungary and by imposing, even in advance of a peace settlement (Hungary is denied an invitation until the Conference is virtually over), even harsher armistice terms. Karolyi flinches from opposing these measures by force. The small socialist element in his government of well-meaning aristocrats defects and forms an alliance with Hungary's fledgling Communist Party. Karolyi resigns and chooses exile. The Communists, led by Bela Kun, take power.